Panel discussion on the future prospect of Arctic research - Enomoto, Hiroyuki; Miyaoka, Hiroshi; Aoki, Teruo; Yamanouchi, Takashi; Yamaguchi, Hajime; Nishimoto, Ketaro; Eicken, Hajo (2020)
The 11th Symposium on Polar Science/Special session: [S] Accelerating Arctic research: Recent progress and future prospect of Arctic research, Tue. 1 Dec. conference object